Programa ANLEDI y hábito y destrezas lectoras - Sanchez Mejia, Julia Pilar (2019)
The present research, entitled: ANLEDI program and habit and reading skills. Case: Students of the first grade of secondary school of the Educational Institution “Marcos Evaristo Villacre” Valle de Nepeña - Chimbote, emerges as an alternative solution to the problem of poor performance of students nationwide and in the Educational Institution "Marcos Evaristo Villacre. The sample population consisted of 22 students of the first grade of secondary education of the Institution, the program of animation to dynamic reading: ANLEDI ", was implemented with a total of twelve sessions. The classic experimental quasi-experimental design, also called the pretest and post test control group respectively, was used. The results indicate that the score obtained after applying the Strategy, statistically significant differences were observed. What allowed us to accept the hypothesis formulated after having applied ANLEDI program ". In conclusion, it is demonstrated that the application of the animation program to dynamic reading: ANLEDI; Significantly improved the dimensions of students' competences, habit and reading skills in students who are in the first grade of secondary education.